EFEKTIFITAS METODE ART-THERAPY TERHADAP PENINGKATAN KEDISIPLINAN BELAJAR SISWA SEKOLAH DASAR - Makhriffah Robbiah Addawiyah; Siti Habibah, Adibah Nur Damiyati, M. Al Afif Annasai, Netty Merdiaty (CV. ADIBA AISHA AMIRA, 2024)
Based on the analysis of the results and discussion, testing the effectiveness of the art therapy method in improving the discipline of grade 3 elementary school students using the Paired Samples T-Test Hypothesis Test, shows that the p value <.001 is smaller than α 0.05. Thus, the hypothesis H0 can be rejected and Ha can be accepted. The significant difference between the pre-test and post-test scores of grade 3 students at SDN 01 Tambun shows the effectiveness of the art therapy method in improving disciplinary behavior in research subjects. An increase in disciplinary behavior was also conveyed by the subject's homeroom teacher after the subject underwent art therapy treatment, although this did not appear significant. The implications of this research can be applied to individuals who experience low levels of discipline.